2017
DOI: 10.1039/c7ee00685c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microstructure on the electron–hole interaction in lead halide perovskites

Abstract: The authors directly show that grain size and quality have a negligible impact on the excitonic characteristics of perovskite semiconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…However, the formation of nonuniformities and pinholes during deposition of thick perovskite films can drastically reduce the device performance. The optimization of thin‐film deposition processes can be supported by specific characterization techniques, allowing for the detection of these imperfections, further improving the growth conditions and further understanding the influence of microstructure …”
Section: Performance Optimizationmentioning
confidence: 99%
“…However, the formation of nonuniformities and pinholes during deposition of thick perovskite films can drastically reduce the device performance. The optimization of thin‐film deposition processes can be supported by specific characterization techniques, allowing for the detection of these imperfections, further improving the growth conditions and further understanding the influence of microstructure …”
Section: Performance Optimizationmentioning
confidence: 99%
“…Moreover, the band gap energy can be tuned in a wide range to meet the demands of a highly efficient solar cell. Theoretical investigations have demonstrated that these multication hybrids can greatly improve the stability and moisture resistance of PSCs [ 19 , 140 , 141 , 142 , 143 ].…”
Section: Hybrid Cations In Perovskites For Improvements In Psc Stamentioning
confidence: 99%
“…The A‐site cation species, including MA, FA, Cs, and their derivatives, have been largely employed to compositionally engineer the halide perovskite materials. [ 32–35 ] Mixing halides leads to variation in the lattice parameters, such as an increase in the cell parameter (5.68 Å→5.92 Å→6.27 Å) when the halide changes (Cl→Br→I) in the cubic phase of MAPbX 3 . [ 36 ] Such halogen mixing method fine tunes the energy gap and effectively enhances the charge transport and device stability.…”
Section: Introductionmentioning
confidence: 99%